Metals and alloys additives as enhancer for rocket propulsion: a review - Ismail, Izham Izzat; Nordin, Norhuda Hidayah; Azami, Muhammad Hanafi; Abdullah, Nur Azam (Semarak Ilmu Publishing, 2022)
A rocket's engine usually uses fuel and oxygen as propellants to increase the rocket's projection during launch. Nowadays, metallic ingredients are commonly used in the rocket’s operation to increase its performance. Metallic ingredients have a high energy density, flame temperature, and regression rate that are important factors in the propulsion process. There is a wide range of additives have been reported so far as catalysts for rocket propulsion. The studies show that the presence of metal additives improves the regression rate, specific impulse and combustion efficiency. Herein, the common energetic additives for rocket propulsion such as metal and light metals are reviewed. Besides the effect of these energetic particles on the regression behaviors of base (hybrid) fuel has been exclusively discussed. This paper also proposed a new alloy namely high entropy alloys (HEAs) as a new energetic additive that can potentially increase the performance of the rocket propellant system.